STUDY ON IN VIVO RELEASE AND IN VIVO ABSORPTION OF CAMPTOTHECIN-LOADED POLYMERIC NANOPARTICLES: LEVEL A IN VITRO -Â IN VIVO CORRELATION - MANIKANDAN, MAHALINGAM; KANNAN, KRISHNAMOORTHY (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objectives: The aim of this study was to develop an in vitro - in vivo correlation (IVIVC) for the prepared Camptothecin (CPT)-loaded polymeric nanoformulation. Methods: In this study, CPT-loaded polymeric nanoformulation was prepared by nanoprecipitation method using containing poly (methacrylic acidco-methyl methacrylate) (polymer), poloxamer 188 (non-ionic surfactant), and β-cyclodextrin (stabilizer). In vitro release rate data were obtained from prepared polymeric nanoformulation using the USP apparatus type 2. A single-dose, crossover pharmacokinetic study for the nanoformulation was carried out in six albino rats. These data were used as the basis for the IVIVC model development. Results: The plasma concentration of CPT was estimated by high-performance liquid chromatography. The pharmacokinetic parameters were calculated from the plasma concentration of CPT and time data. Furthermore, the deconvolution of the in vivo concentration-time data was performed using Wagner–Nelson method to estimate the in vivo drug release profile. Conclusion: Therefore, a level A IVIVC was developed for CPT-loaded polymeric nanoformulation between dissolution percentage and intestinal absorption in rats. The simplest way to demonstrate a correlation is to plot the percentage absorbed in vivo versus the percentage released in vitro at the same time. Keywords: Camptothecin, In vitro - in vivo correlation, Wagner–Nelson, Dissolution, Pharmacokinetics.